Coronary haemodynamics in patients with severe aortic stenosis and coronary artery disease undergoing Transcatheter Aortic Valve Replacement: implications for clinical indices of coronary stenosis severity - Ahmad,Y; Gotberg,M; Cook,C; Howard,J; Malik,I; Mikhail,G; Frame,A; Petraco,R; Rajkumar,C; Demir,O; Iglesias,JF; Bhindi,R; et al. (JACC: Cardiovascular Interventions, 2018)
Objectives In this study, a systematic analysis was conducted of phasic intracoronary pressure and flow velocity in patients with severe aortic stenosis (AS) and coronary artery disease, undergoing transcatheter aortic valve replacement (TAVR), to determine how AS affects 1) phasic coronary flow; 2) hyperemic coronary flow; and 3) the most common clinically used indices of coronary stenosis severity, instantaneous wave-free ratio and fractional flow reserve.Background A significant proportion of patients with severe aortic stenosis (AS) have concomitant coronary artery disease. The effect of the valve on coronary pressure, flow, and the established invasive clinical indices of stenosis severity have not been studied.Methods Twenty-eight patients (30 lesions, 50.0% men, mean age 82.1 ± 6.5 years) with severe AS and coronary artery disease were included. Intracoronary pressure and flow assessments were performed at rest and during hyperemia immediately before and after TAVR.Results Flow during the wave-free period of diastole did not change post-TAVR (29.78 ± 14.9 cm/s vs. 30.81 ± 19.6 cm/s, p = 0.64). Whole-cycle hyperemic flow increased significantly post-TAVR (33.44 ± 13.4 cm/s pre-TAVR vs. 40.33 ± 17.4 cm/s post-TAVR, p = 0.006); this was secondary to significant increases in systolic hyperemic flow post-TAVR (27.67 ± 12.1 cm/s pre-TAVR vs. 34.15 ± 17.5 cm/s post-TAVR, p = 0.02). Instantaneous wave-free ratio values did not change post-TAVR (0.88 ± 0.09 pre-TAVR vs. 0.88 ± 0.09 post-TAVR, p = 0.73), whereas fractional flow reserve decreased significantly post-TAVR (0.87 ± 0.08 pre-TAVR vs. 0.85 ± 0.09 post-TAVR, p = 0.001).Conclusions Systolic and hyperemic coronary flow increased significantly post-TAVR; consequently, hyperemic indices that include systole underestimated coronary stenosis severity in patients with severe AS. Flow during the wave-free period of diastole did not change pos